D4N2024 Presentation Showcase – Thematic Session 5b: Addressing nutrition challenges in vulnerable populations - Thapaliya, Pragya; Sheuly, Afsana Habib; Gadhavi, Alfa; El-Kour, Tatyana; Akter, Fahmida; Das, Pinaki; Dirghayu, K. C.; Shirisha, P.; Rinky, Farhana; Kumar, Raj; Yasin, Rahima (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – Thematic Session 5b: Addressing nutrition challenges in vulnerable populations